Intervensi digital, peran pengawas minum obat (PMO), dan pendekatan psikososial dalam meningkatkan kepatuhan pengobatan tuberkulosis: Literature review - Indah Mutia; Andi Alim; Ishaq Iskandar (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Tuberculosis (TB) remains a major global public health challenge, particularly in low- and middle-income countries, where suboptimal treatment adherence continues to hinder therapeutic success. Non-adherence contributes to treatment failure, drug resistance, relapse, and ongoing community transmission. Purpose: To synthesize scientific evidence on the effectiveness of digital interventions, the role of Medication Supervisors (PMOs), and psychosocial and community empowerment approaches in improving TB treatment adherence and success. Method: A narrative structured review guided by systematic review principles was conducted, including 28 studies published between 2016 and 2025. Results: The findings indicate that digital interventions—such as SMS reminders, video-observed therapy, and mobile health applications—enhance adherence through reminders, patient education, monitoring, and improved communication; however, their impact on clinical outcomes remains moderate and implementation-dependent. Conversely, treatment supporters, family engagement, and community participation play a pivotal role in sustaining adherence, strengthening patient motivation, and improving quality of life. Psychosocial and community-based strategies further reinforce medical interventions by reducing stigma, improving health literacy, and establishing sustainable social support networks. Conclusion: Overall, improving TB treatment adherence and outcomes requires a multidimensional and context-specific approach integrating digital health technologies, strengthened treatment support systems, and psychosocial and community-level interventions.   Keywords: Community Empowerment; Digital Health; Psychosocial Interventions; Tuberculosis; Treatment Adherence; Treatment Supporters.